The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.12697/akut.2009.14.01
|View full text |Cite
|
Sign up to set email alerts
|

Thermal "portrait" of sportsmen with different aerobic capacity

Abstract: In Games and Sports the importance of aerobic potential has been realized by top coaches and everyone tends to spur it up to perform efficiently. A group of 40 male students who were in the age group of 17to 25 years were selected as subjects for the study. They were divided into two groups of 20 each (n= 20) as low and high aerobic capacity groups based on Cooper's 12 minutes run and walk test. Physiological traits were estimated and studied descriptively. The results showed the mean value of lean body mass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Skin surface temperature is one of the most important indicators for assessing the human thermal physiological state and the effectiveness of the thermoregulatory system (1,2). Several applications of skin temperature measurement have been identified in research fields, such as clinical diagnosis (3,4), sports physiology (2,6,7), environmental building ergonomics (8), and clothing design with adapted thermal properties (9).…”
Section: Introductionmentioning
confidence: 99%
“…Skin surface temperature is one of the most important indicators for assessing the human thermal physiological state and the effectiveness of the thermoregulatory system (1,2). Several applications of skin temperature measurement have been identified in research fields, such as clinical diagnosis (3,4), sports physiology (2,6,7), environmental building ergonomics (8), and clothing design with adapted thermal properties (9).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of various parts of the body is an important parameter in the evaluation of human adaptation to different environmental conditions and muscle activities (Akimov et al, 2009;Chudecka & Lubkowska, 2012;Fernández-Cuevas et al, 2015;Kenney & Munce, 2003;Novotny et al, 2015;Torii et al, 1992;Zontak et al, 1998). Thermography is a non-invasive technique that can reveal and visualize differences in temperature distribution on the skin surface of an individual (Torii et al, 1992;Zontak et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies applying infrared thermography have been devoted to sports performance and sports pathology diagnostics (Akimov et al, 2009;Coh &Širok, 2007;Hildebrandt et al, 2012;Novotny et al, 2015), there are some investigations that have confirmed beneficial health outcomes associated with SAT in adults (Drobnik-Kozakiewicz et al, 2013;Forte et al, 2001;Kravitz et al, 1993;Mori et al, 2006;Zuzda & Latosiewicz, 2013). These studies, however, did not evaluate SAT's effects on the temperature of the deep muscles of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that massage affects not only structural layers of the skin but also CNS activity through numerous extra-and interoreceptors. Even the slightest changes in the nervous system are reflected in the receptor apparatus of the skin and visa versa, the changes occurring in the skin under a temperature stimulus affect the CNS functioning (Akimov, Andreev, Arkov, 2009;Chudecka, Lubkowska, 2010). Massage improves the skin and muscle tone ROMANNA RUDENKO, ANATOLIY MAHLIOVANYY, OLENA SHYYAN, TETYANA PRYSTUPA -------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------…”
Section: Discussionmentioning
confidence: 99%